2007
DOI: 10.1128/iai.01183-06
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Characterization of the Superantigen Streptococcal Pyrogenic Exotoxin G from Streptococcus dysgalactiae

Abstract: We identified seven novel variants of streptococcal pyrogenic exotoxin G (SPEGG), a superantigen, in Streptococcus dysgalactiae subsp. dysgalactiae or equisimilis isolates from clinical cases of infection in humans and animals. Phylogenetic analysis of the SPEGG variants indicated two clades in the dendrogram: one composed of variants derived from the bacteria isolated from the humans and the other composed of variants from the bacteria isolated from the animals. Bovine peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…By using other primers (designed in this study) targeting the speM and speK genes of S. pyogenes and spegg of S. dysgalactiae subsp. equisimilis (73), eight bovine isolates that carried speK, one bovine isolate that carried speM, one bovine isolate that carried speK and speM, and five human isolates that carried spegg were found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using other primers (designed in this study) targeting the speM and speK genes of S. pyogenes and spegg of S. dysgalactiae subsp. equisimilis (73), eight bovine isolates that carried speK, one bovine isolate that carried speM, one bovine isolate that carried speK and speM, and five human isolates that carried spegg were found.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was not clear how many isolates carried the speG gene by both the array and PCR amplification results. The latter may be due to a lack of homology between the primers used and the speG gene of S. dysgalactiae (named spegg), as variants of this gene may occur (73). By using other primers (designed in this study) targeting the speM and speK genes of S. pyogenes and spegg of S. dysgalactiae subsp.…”
Section: Resultsmentioning
confidence: 99%
“…However, scarce occurrences of SDSE strains have been described, having one of those genes [32,43]. The only superantigen gene which is often found in SDSE strains is spe G, which encodes exotoxin G [12,22,24,32,35,36,[39][40][41][42]44]. Between both of these closely related bacteria, interspecies DNA transfer occurs [6,45,46] by means of mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%
“…Three cases of iatrogenic SDSE infection following transfusion of platelet concentrates were described [19], as well as cases of nosocomial infections [30]. It was found that most patients with invasive infections caused by SDSE were suffering from additional disorders, especially with cardiovascular diseases of atherosclerotic etiology, diabetes, obesity, [72,73], dogs [74], camels [75], cattle [44] and sea otters [76]. Marked differences have been found between SDSE strains deriving from humans and animals [44,73].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation